Diverse Mobile Genetic Elements and Conjugal Transferability of Sulfonamide Resistance Genes (sul1, sul2, and sul3) in Escherichia coli Isolates From Penaeus vannamei and Pork From Large Markets in Zhejiang, China - Jiang, Han; Cheng, Hui; Liang, Yi; Yu, Shengtao; Yu, Ting; Fang, Jiehong; Zhu, Cheng (Frontiers in Microbiology, 2019)
High prevalence rates of sulfonamide resistance genes sul1, sul2 and sul3 have been observed in Gram-negative bacteria isolated from humans, domestic animals and aquaculture species worldwide. We investigated the distribution characteristics, location, conjugative transferability and genetic environments of sul genes from Escherichia coli isolates collected from Penaeus vannamei and pork samples from three large markets in Zhejiang, China. The prevalence rates of sul genes in sulfonamide-resistant E. coli isolates from P. vannamei and pork samples were 90.0% and 88.6%, respectively, and the prevalence of sul1 and sul2 was significantly higher than that of sul3 (p < 0.05). Twenty-four representative sul-positive E. coli isolates were analyzed in detail. Southern blot hybridization confirmed that sul genes of E. coli isolates were located on plasmids and/or chromosomes. Transfer of resistance through conjugation was observed in all 18 E. coli isolates harboring sul genes on plasmids. Replicon typing identified seven different incompatibility groups and IncF was the dominant replicon type among sul gene-containing plasmids from both sources. PCR walking analysis indicated that 87.5% (35/40) of sul gene-related fragments carried insertion sequences (ISs) belonging to a variety of families in diverse sites, with IS26 occurring most frequently. In addition, the sul1 gene was detected mainly in fragments carrying class 1 integrons. Co-location on the same fragment with resistance genes that may contribute to the persistence and dissemination of sul1 and/or sul2 genes. The diversity of mobile genetic elements and resistance genes adjacent to sul3 was much lower than those adjacent to sul1 and sul2, especially those located in chromosomes, which reduced the transmission potential of the sul3 gene. In conclusion, combined with the results of clonal relatedness analysis by PFGE and MLST of 24 representative E. coli isolates from P. vannamei and pork samples, it showed that a small number of sul genes were vertically transmitted among E. coli from P. vannamei and that horizontal gene transfer was likely the main transmission mechanism of sul genes from both sources. Our results provide important information to better understand the risk of transmission of sul genes from seafood and meat to humans.